TERMINOLOGICAL CONFUSION AROUND THE ISSUE OF VERBAL- VISUAL RELATIONS: EKPHRASIS AND INTERSEMIOTICITY, INTERMEDIALITY, PICTORIALISM, ICONICITY - Słodczyk, Rozalia (Porównania, 2019)
This article focuses on the relationship between the sphere of the word and the domain of the image. It presents the terms associated with verbal-visual connections employed in the field of literary, comparative and interdisciplinary research. Attention is drawn to the multiplicity of concepts in use; the article juxtaposes them with each other, identifies their connotations, determines whether they are operational and comments on their possible synonymity. In particular, the paper analyses the terms ‘intersemioticity’, ‘interartisticism’ and ‘intermediality’ as well as ‘pictorialism’, ‘imagery’ and ‘iconicity’; it also discusses the notion of pictorial allusion. Apart from organizing the research field and turning a spotlight on important studies less known in Polish scholarly literature, the aim is to locate the phenomenon of ekphrasis in this terminological network.